Analysis of Vegetable Farmer's Business Development Strategy in Sumber Urip Village Selupu Rejang Sub-District Rejang Lebong District - Witra, Yelfida; Hadi, Ode Sofyan (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
This study aims to describe the right strategy in developing vegetable farming in Sumber Urip Village, Selupu Rejang District based on internal and external factors. The problem in this research is unstable prices, pests and plant diseases, still using simple technology, etc. The prospect of vegetable farming in Sumber Urip Village is quite promising because of requests from outside Bengkulu such as Palembang, Jambi and Bangka. Therefore the right strategy is needed in an effort to develop the farming business. Samples are taken at random. The data is processed using SWOT analysis. The results of this study are the description of the results of the SWOT analysis in the form of a strategy used to develop vegetable farming in Sumber Urip Village.